Crisis Stability and Long-Range Strike - Morgan, Forrest E. (RAND Corporation, 2023)
To effectively manage an international crisis, the United States must balance its threats with restraint. It must posture forces in ways that deter aggression without implying that an attack is imminent, while limiting its own vulnerability to surprise attack. A RAND study sought to identify which long-range strike assets—strike fighters, bombers, ballistic missiles, cruise missiles—offer capabilities most conducive to stabilizing such crises.